Ototoxicity of Non-aminoglycoside Antibiotics - Rybak, Leonard P.; Ramkumar, Vickram; Mukherjea, Debashree (Frontiers in Neurology, 2021)
It is well known that aminoglycoside antibiotics can cause significant hearing loss and vestibular deficits that have been described in animal studies and in clinical reports. The purpose of this review is to summarize relevant preclinical and clinical publications that discuss the ototoxicity of non-aminoglycoside antibiotics. The major classes of antibiotics other than aminoglycosides that have been associated with hearing loss in animal studies and in patients are discussed in this report. These antibiotics include: capreomycin, a polypeptide antibiotic that has been used to treat patients with drug-resistant tuberculosis, particularly in developing nations; the macrolides, including erythromycin, azithromycin and clarithromycin; and vancomycin. These antibiotics have been associated with ototoxicity, particularly in neonates. It is critical to be aware of the ototoxic potential of these antibiotics since so much attention has been given to the ototoxicity of aminoglycoside antibiotics in the literature.